PERBEDAAN HASIL PEMBELAJARAN EKONOMI DENGAN MENGGUNAKAN METODE PEMBELAJARAN TIME TOKEN DAN THINK TALK WRITE - Erma Yulaini; Dhiana Whidhi; Elin Sartika (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2020)
The purpose of this study was to determine the differences between student learning outcomes using the Time Token learning model using the Think Talk Write learning model on economic lessons on SMA Negeri 8 Prabumulih. The variable of this study consisted of two independent variables namely the learning outcomes of students who were taught using the Time Token learning method and Think Talk Write learning method. The research sample was 50 students. Data collection techniques use documentation, observation and tests, while data analysis techniques use the t test. Based on the results of the observations obtained the average time Token group learning activities amounted to 72.99% with the active category lower than the average Think Talk Write group of 81.34% which is also included in the category of active categories. Based on the results of the study it was obtained that the average student learning outcomes after being applied to the Time Token learning method of 70.45 were categorized as good, while the average Think Talk Write learning method of 78.84 was also categorized as good. Based on the results of the t test, the value of tcount is 4.75> ttable is 1.677224, so it was concluded that there was a difference between student learning outcomes using the Time Token learning method using the Think Talk Write learning method on economic lessons on SMA Negeri 8 Prabumulih.